2021
DOI: 10.1002/tee.23523
|View full text |Cite
|
Sign up to set email alerts
|

Robot Ego‐Noise Suppression with Labanotation‐Template Subtraction

Abstract: In this study, we aim to improve automatic-speech-recognition (ASR) accuracy in the presence of robot ego-noise toward a better human-robot interaction. Although several noise reduction methods have been proposed to increase ASR accuracy or signal-to-noise ratio (SNR) by predicting ego-noises through a short-time motion-template subtraction or a neural network, these methods showed poor performance in some practical use cases, such as attenuating long-term motion-associated ego-noise. Based on the motion-templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…As part of our efforts to develop a realistic robotic operation system, we have integrated the proposed system with a learning-from-observation system (Fig. 17) that includes a speech interface [44], [45], a visual teaching interface [33], a reusable library of robot actions [46], and a simulator for testing robot execution [47]. Please refer to the respective papers for the results of robot execution, as it is beyond the scope of this paper.…”
Section: Discussion: Towards More General Robotic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our efforts to develop a realistic robotic operation system, we have integrated the proposed system with a learning-from-observation system (Fig. 17) that includes a speech interface [44], [45], a visual teaching interface [33], a reusable library of robot actions [46], and a simulator for testing robot execution [47]. Please refer to the respective papers for the results of robot execution, as it is beyond the scope of this paper.…”
Section: Discussion: Towards More General Robotic Applicationsmentioning
confidence: 99%
“…The user sends a query to the robot system via text or microphone input. Microphone input is noise-suppressed to prevent the robot's ego noise from interfering with recognition [7], [8]and then converted to text using a third-party text-to-speech technology [9]. The robot system then generates a prompt for the GPT-3/ChatGPT model based on this input.…”
Section: Pipelinementioning
confidence: 99%
“…As part of our efforts to develop a realistic robotic operation system, we have integrated our proposed task planner with a learning-from-observation system (Fig. 19) incorporating a speech interface [45], [46], a visual teaching interface [47], a reusable robot skill library [48], [49], and a simulator [50]. The code for the teaching system is available at: https://github.com/microsoft/ cohesion-based-robot-teaching-interface.…”
Section: Connection With Vision Systems and Robot Controllersmentioning
confidence: 99%
“…Most prior research on the factors that affect ASR has focused on noise, speaker accent, speaker age, and multiple speakers. Noise persists as a significant hurdle to developing ASR, and many approaches have been proposed to enhance the robustness of ASR systems [18,19]. Our previous study suggested a method to associate the Articulation Index to estimate the influence of stationary noise on the ASR word accuracy (ACC) [20].…”
Section: Introductionmentioning
confidence: 99%